PEMANFAATAN LIMBAH KULIT BAWANG MERAH SEBAGAI KANDIDAT INGRIDIEN MINUMAN FUNGSIONAL ANTIOKSIDAN - Rianita Pramitasari; Lidwina Krisna Chrysanti (Jurnal Perkotaan, 2020)
Shallot is widely used in culinary purpose. However, the use of shallot produces a lot of waste. Shallot skin contains anthocyanin, which has antioxidant activity. This study aimed to evaluate different solvents and extraction times for anthocyanin extraction from shallot skin, to evaluate different drying methods, and to evaluate the physicochemical properties of the anthocyanin powder. Chemical tests were conducted before and after drying, including total anthocyanin content, antioxidant activity using DPPH, total phenolic, and total flavonoid content. Physical tests were undertaken only after drying, including moisture content, water activity, viscosity, solubility, and colour. Extraction with citric acid solvent in 72h extract resulted in the highest total anthocyanin than water and acetic acid solvent. After drying, the highest total anthocyanin was obtained from foam mat drying method, which extracted using citric acid solvent. While antioxidant activity was not significantly differenced among samples. Physical test for the powders showed low moisture content and water activity, red colour index, as well as suitable viscosity and solubility results. In conclusion, anthocyanin powder from shallot skin has a potent as a functional antioxidant ingredient that can be applied in beverage products.